‘Emptiness’ and ‘Nothingness’ as Key Elements to Conveying and Understanding Meaning in Japanese Calligraphy - Tudorică, Ioana-Ciliana (Eikón / Imago, 2023)
The article analyses one of Japanese calligraphy’s (shodō 書道) particularities: the notion of “emptiness”, “nothingness”. This concept can be observed in different layers of the art: from the white of the paper, to the movement of the brush after it has been lifted from the paper to the interpretative process. In this way, there are instances of “emptiness” during several stages of creation and understanding of a calligraphic work. In order to illustrate this, our article will analyse two shodō 書道 works, pinpointing the use of “emptiness”, or “nothingness”, and the effect they create for the calligraphic work as a whole. We conclude that in order to grasp the transcendent meaning, one must take into account all elements present within a calligraphic work, including the instances of “emptiness”.